Brain‐Wide Monitoring of Antibody Therapeutics Crossing the Blood‐Brain‐Barrier. (20th December 2022) - Redd, Chase; Guanzon, Nathaniel; Gallegos, Yessenia; Weiss, Jacob; Jensen, Camilla Stampe; Vergo, Sandra B.; Wheeler, Damian G.
Abstract: Background: Recent advances in optical clearing and light sheet imaging have opened an exciting new avenue for brain‐wide, cellular resolution immunostaining at the forefront of a dimensional shift from 2D to 3D histology. Providing access to the intricate anatomy of the whole intact brain, tissue clearing offers neuroscientists unbiased and complete views of brain anatomy and function. One area where these methods have particular utility is in the development of CNS therapeutics where they can be used to examine the regional distribution of the therapeutic in the brain as well as brain‐wide target engagement and phenotypic efficacy. Method: We have developed an optimized iDISCO‐based clearing method and with our Mesoscale Imaging System for ZEISS Lightsheet microscopes, we can image cellular‐resolution immunoreactivity across entire mouse brains in ∼25 min. Here we examined whether our technology can detect antibody therapeutics crossing the blood‐brain‐barrier. To do this, we took advantage of a bispecific antibody engineered to bind to the Alzheimer's Disease target, BACE1, as well as the transferrin receptor (TfR1), which helps shuttle the antibody across the brain endothelium and into the brain parenchyma. Twenty‐four hours after dosing we perfusion‐fixed the brains and performed our modified iDISCO‐based clearing and staining protocol using 3 different anti‐human IgG secondary antibodies. Result: We found anti‐human antibodies revealed high levels of the bi‐specific antibody in the brain vasculature and parenchyma. Importantly, in brains dosed with a monospecific control antibody that does not bind TfR1, immunoreactivity was at background levels, similar to that seen in control mice that were not dosed with antibody. These data are consistent with binding to TfR1 localizing the bispecific antibody in the vasculature and enabling transport into the brain parenchyma. Importantly, the pattern of immunoreactivity in the cleared brain matched the pattern seen with traditional 2D slice immunohistochemistry. But unlike traditional methods, we were able to examine the concentration of the bi‐specific antibody throughout the entire brain and assess whether the pattern matched that of the therapeutic target. Conclusion: Together, these data provide a clear demonstration of the utility of tissue clearing methods for quantitative brain‐wide monitoring of therapeutic antibody exposure.